Decreasing costs of renewables: Analysis of energy sector planning and climate policy in Mexico - Johannes Eckstein; Marie-Jeanne Kurdziel; Jose Antonio Ordonez (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2020)
Mexico is signatory to the Paris Agreement. As such, the country submitted its first Nationally Determined Contribution (NDC) in 2014 in the run-up to the Paris agreement. In the past years, renewable energy systems have seen a massive cost reduction, which should be considered energy sector and climate change mitigation plans (also see Eckstein et al. (2020)). In view of these developments, this study analyses the process underlying the development of Mexico's NDC and its revision in 2020 with a particular focus on the energy sector and renewable energy systems. The assumptions underlying the related energy sector planning document (PRODESEN) and the relationships to the NDC are assessed. The study is completed by giving a snapshot of political constraints under the current administration of President López Obrador. The study builds on literature review and insights gained from interviews with pertinent Mexican stakeholders. In Mexico's NDC, emissions are estimated to increase by roughly 50% between 2013 and 2030 in the business as usual (BAU) scenario. The unconditional mitigation target of Mexico's NDC foresees a greenhouse gas (GHG) emissions reduction by 22% by 2030 relative to BAU. In the electricity sector, the NDC aims at a 31% GHG emissions reduction. The target setting process remains publicly undisclosed and highly politicized. The main responsibility for the NDC revision is with the Environment Ministry of Mexico (SEMARNAT). SEMARNAT is supported by the National Institute for Ecology and Climate Change (INECC), a body created under the climate change law. The highest level administrative body in the energy sector in Mexico is the Energy Ministry (SENER), responsible for the establishment of targets and strategic transmission investments for renewable energy. The 2020 NDC revision considers only enhanced energy efficiency measures and to a large extent disregards renewable energies in the power sector. Energy sector planning is described to align to political interests and not to follow cost optimization, despite the fact that cost optimization modelling exercises have been carried out by SENER and supported by international organizations. [...]
urn:nbn:de:0011-n-6156279
Keywords: 330